A fault recovery strategy of flexible interconnected distribution network with SOP flexible closed-loop operation - Zhao, Yuduo; Xiong, Wei; Yuan, Xufeng; Zou, Xiaosong (International journal of electrical power & energy systems, 2022)
•Introduce the chance constrained programming to deal with the randomness of wind power, photovoltaic output and load.•The fault recovery capability of flexible interconnected distribution network considering closed-loop operation is more fully developed.•Analyze the fault recovery effect of flexible interconnected distribution network under different SOP control modes and propose a two-stage recovery strategy.•Considering more complex faults of flexible interconnected distribution network, provide an effective fault recovery strategy for concurrent faults. With the continuous exploration of the application value of flexible interconnected distribution network, Soft Open Point (SOP) as its core device, how to fully explore the self-healing control support capability of SOP and improve its power supply reliability becomes particularly important. Aiming at the problem of fault recovery of flexible interconnected distribution network with multiple AC power supply areas, firstly, the topology of flexible interconnection of distribution network and the fault recovery model of SOP are described. Secondly, the stochastic nature of wind power, photovoltaic output and load is considered, and then the chance-constrained programming is introduced to deal with. Then, aiming at the coordinated operation of flexible closed-loop network in multiple AC power supply areas, and introducing the constraint on the acting number of switches, a stochastic optimization model of flexible interconnected distribution network fault recovery is established, and then the model is transformed into a deterministic mixed integer second-order cone programming model, which can be solved by CPLEX solver. Finally, the proposed model has been tested on a modified hand-in-hand IEEE33 system with dual-terminal SOP, verifying that the strategy proposed in this paper can effectively solve the fault recovery problem of flexible interconnected distribution network with multiple AC power supply areas considering uncertainty, and showing that this strategy can maximize the self-healing capability of distribution system.